Dimensionamento de pessoal de enfermagem em unidades pediátricas hospitalares e o cuidado centrado na família: percepção de gestores - Ramos, Aline Landim (2022)
The quality and safety of nursing care in a pediatric hospital unit involves the dimensioning of nursing staff and the incorporation of the philosophy “care centered on the person of the child and the family”. The objective of this study was to know the perceptions of managers of pediatric hospital units, about the dimensioning of nursing staff and its implications for family-centered care. This is a qualitative study, developed with nine nurses with experience in managing pediatric hospitals, located using the snow ball technique. A single semi-structured interview, conducted remotely, using the Google Meet platform, the strategy adopted for data collection. Their average duration was 20 minutes and all interviews were developed by the researcher who authored this study. The thematic analysis in Braun & Clarke's proposal was conducted, supported by the theoretical framework of Symbolic Interactionism. Data collection took place from January to September 2021. The results are presented from two thematic units: “Weaknesses of patient classification systems and creation of adjustments” and “Thinking about Family-Centered Care and its incorporation” in the dimensioning of nursing staff”. The first unit reveals the perception that the national instrument for classifying pediatric patients is fragile, lacking in the consideration of specific characteristics and particularities of nursing work, when there is an emphasis on family demands and care for the child's family member/companion. Given this understanding, the manager does not faithfully adopt the instrument, but adjusts its result based on elements related to these weaknesses and the context of care. Although the family member is recognized, his/her insertion in the care setting was described in the direction of health education and with little intention of building collaborative relationships that make him/her at the center of care. The manager's actions were not evidenced to correlate the reception of the family member and the dimensioning of the nursing staff. The workload placed on the nursing professional, in the daily practice of health care, in pediatric units is related to the quality and safety of care. The study developed contributed to the discussion on the sizing of nursing staff in pediatric units, which has revealed timid advances since the proposal of the Brazilian pediatric patient classification instrument, in 2014. It also brings elements for the articulation between staff sizing of nursing with family-centered care, a pressing aspect, otherwise families will continue to be denied or reduced to people who provide child care and need to be trained for it.